Clinical and prognostic implications of an immune‐related risk model based on TP53 status in lung adenocarcinoma. Issue 2 (8th December 2021) - Song, Xuming; Chen, Qiang; Wang, Jifan; Mao, Qixing; Xia, Wenjie; Xu, Lin; Jiang, Feng; Dong, Gaochao
Abstract: TP53  mutation is the most widespread mutation in lung adenocarcinoma (LUAD). Meanwhile, p53 (encoded by TP53 ) has recently been implicated in immune responses. However, it is still unknown whether TP53  mutation remodels the tumour microenvironment to influence tumour progression and prognosis in LUAD. In this study, we developed a 6‐gene immune‐related risk model (IRM) to predict the survival of patients with LUAD in The Cancer Genome Atlas (TCGA) cohort based on TP53  status, and the predictive ability was confirmed in 2 independent cohorts. TP53  mutation led to a decreased immune response in LUAD. Further analysis revealed that patients in the high‐index group had observably lower relative infiltration of memory B cells and regulatory T cells and significantly higher relative infiltration of neutrophils and resting memory CD4 + T cells. Additionally, the IRM index positively correlated with the expression of critical immune checkpoint genes, including PDCD1 (encoding PD‐1) and CD274 (encoding PD‐L1), which was validated in the Nanjing cohort. Furthermore, as an independent prognostic factor, the IRM index was used to establish a nomogram for clinical application. In conclusion, this IRM may serve as a powerful prognostic tool to further optimize LUAD immunotherapy.